Perovskite quantum dot glass luminescent material as well as preparation method and application thereof
By optimizing the calcination conditions, perovskite quantum dots are embedded in lithium disilicate glass ceramics to form perovskite quantum dot glass composite luminescent material with wide excitation peaks and small Stokes displacements, solving the energy absorption of perovskite quantum dots The problem of low energy utilization efficiency achieves efficient green light emission and stability in the field of display lighting.
Patent Information
- Application Number
- CN202411636210.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When existing perovskite quantum dots absorb energy, only a small part of the energy is used to emit light, and the excitation spectrum will decrease after high-energy excitation, and there is no reported wide excitation peak and small Stokes displacement phenomenon.
By optimizing the reaction process of perovskite quantum dots, the perovskite quantum dots were successfully embedded in lithium disilicate glass ceramics, forming a wide excitation peak of 275-450nm and a small Stokes small Displaced perovskite quantum dot glass composite luminescent material.
A single green light emission under near-ultraviolet or blue light excitation is achieved. The peak width of the green light emission peak is narrow, suitable for display lighting fields, and maintain stability in polar solvents.
Smart Images

Figure CN119285225A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of luminescent materials, and in particular relates to a perovskite quantum dot glass composite luminescent material and a preparation method and application thereof. Background Art
[0002] Metal halide perovskite quantum dots (PQDs) have attracted widespread attention due to their advantages such as low cost, high absorption coefficient, narrow fluorescence emission half-peak width, adjustable Stokes shift, and simple synthesis. These characteristics make perovskite quantum dots considered as high-quality candidate materials for the next generation of solar cells and light-emitting diodes (LEDs). At present, there have been some reports on embedding perovskite quantum dots into glass matrices, thus solving the problem of poor stability of perovskite quantum dots to air, temperature, polar solvents and light irradiation due to colloidal properties and variable crystallization. However, the Stokes shift reported so far is still mainly based on an emission wavelength of about 520nm and an excitation wavelength of about 365nm, with a peak difference of about 155nm. The large Stokes shift indicates that only a small part of the absorbed energy is used for luminescence. In addition, the reported excitation spectrum shows a significant downward trend after passing the 365nm peak, while the phenomenon of a wide excitation peak and a small Stokes shift has not been reported. Summary of the invention
[0003] The purpose of the present invention is to provide a perovskite quantum dot glass composite luminescent material and its preparation method and application. A stable, high-luminescent perovskite quantum dot glass ceramic material is synthesized at high temperature, and the calcination temperature, calcination time and the influence of different concentrations on the reaction process, crystal structure, micromorphology and optical properties of the perovskite quantum dots are optimized. The perovskite quantum dots are successfully coated with a glass matrix, and the obtained composite luminescent material has a wide excitation peak of 275 to 450 nm and a small Stokes shift.
[0004] In order to achieve the above object, the technical solution of the present invention is as follows:
[0005] On the one hand, the present invention provides a perovskite quantum dot glass composite luminescent material, wherein the luminescent material comprises perovskite quantum dots and lithium disilicate glass ceramics, wherein the chemical formula of the perovskite quantum dots is K x Cs 1-x PbB 3 , 0.2≤x≤0.4, and the mass of the perovskite quantum dots is 10 to 70% of the mass of the lithium disilicate glass ceramic.
[0006] In the above technical solution, further, the average particle size of the perovskite quantum dots is 2 to 7 nm.
[0007] In the above technical solution, further, when excited at 275-450nm, green light with a peak wavelength at 511-519nm is emitted.
[0008] Another aspect of the present invention provides a method for preparing the composite luminescent material, the method comprising the following steps:
[0009] (1) Li 2 CO 3 , Rb 2 CO 3 NH 4 H 2 PO 4 、Al 2 O 3 、SiO 2 ,La 2 O 3 、CeO 2 、ZrO 2 Grinding and mixing evenly to obtain glass ceramic raw materials;
[0010] (2) melting the glass ceramic raw material obtained in step (1) in a muffle furnace to obtain molten glass, then quenching the molten glass with water to obtain a glass block, drying the glass block, and grinding it to obtain glass powder;
[0011] (3) The glass powder obtained in step (2) is mixed with KBr, CsBr, PbBr 2 The mixture is mixed and ground evenly, and heat-treated in a muffle furnace to obtain a perovskite quantum dot glass composite luminescent material.
[0012] In the above technical solution, further, in step (2), the melting temperature is 1200-1800° C., and the insulation time is 30-80 min.
[0013] In the above technical solution, further, in step (3), the temperature of the heat treatment is 500-700° C., and the time of the heat treatment is 180-300 min.
[0014] In the above technical solution, further, the Li 2 CO 3 , Rb 2 CO 3 NH 4 H 2 PO 4 、Al 2 O 3 、SiO 2 ,La 2 O 3 、CeO 2 、ZrO 2The mass ratio is 10-15:10-15:5-10:1-5:45-60:5-15:1-5:1-5;
[0015] The glass powder, KBr, CsBr, PbBr 2 The mass ratio is 58.8~91:0.5~2.2:2.5~11.8:6~27.2.
[0016] The present invention also provides an application of the above-mentioned composite luminescent material in lighting devices and display devices. In the lighting device, the prepared composite luminescent material is mixed with ultraviolet-curable organic silica gel and then encapsulated on a 365-450nm ultraviolet or blue light chip, so that it can obtain bright green light after excitation.
[0017] In the above technical solution, further, in the lighting device, the prepared composite luminescent material is mixed with UV-curable organic silica gel and then encapsulated on a 365-450nm UV or blue light chip, so that it can obtain bright green light after excitation.
[0018] The beneficial effects of the present invention are:
[0019] 1. The preparation method of the present invention has simple process, high photoluminescence intensity, low equipment requirements, wide excitation spectrum, small Stokes shift, environmental friendliness, and good industrialization and application prospects.
[0020] 2. The perovskite quantum dot glass composite luminescent material obtained by the present invention can be used in display lighting devices. It can achieve single green light emission under near-ultraviolet light or blue light excitation. The peak width of the green light emission peak is narrow (the half-peak width is only about 20 to 50 nm) and has good monochromaticity, which is conducive to its application in the field of display lighting.
[0021] 3. The perovskite quantum dot glass composite luminescent material obtained by the present invention has a wide excitation peak (275-450 nm), and can therefore be effectively excited by near-ultraviolet light or blue light of more wavelengths.
[0022] 4. The present invention improves the stability of perovskite quantum dots by coating with lithium disilicate glass ceramics, so that the perovskite quantum dots can maintain a certain strength even in polar solvents. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0024] Figure 1 The transmission electron microscope image and particle size statistics graph of the sample obtained in Example 3, a is the transmission electron microscope image, and b is the particle size statistics graph;
[0025] Figure 2 The excitation spectra of the samples prepared in Example 3, Example 6 and Example 7 under 517 nm wavelength monitoring and the emission spectra under 365 nm wavelength excitation, a is the excitation spectrum, b is the emission spectrum;
[0026] Figure 3 This is a photo of the sample prepared in Example 3 being mixed with UV-curable organic silica gel and then packaged in a 365nm UV chip and then excited;
[0027] Figure 4 This is a photo of the sample prepared in Example 3 being mixed with deionized water and irradiated with a 365nm ultraviolet lamp. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with embodiments, but the protection scope of the invention is not limited thereto.
[0029] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.
[0030] Example 1
[0031] Table 1
[0032] raw material Weight(g) <![CDATA[SiO 2 ]]> 17.4 <![CDATA[Li 2 CO 3 ]]> 4.3 <![CDATA[Al 2 THE 3 ]]> 0.9 <![CDATA[Rb 2 CO 3 ]]> 4.7 <![CDATA[NH 4 H 2 PO 4 ]]> 2.6 <![CDATA[La 2 THE 3 ]]> 3.5 <![CDATA[CeO 2 ]]> 0.8 <![CDATA[ZrO 2 ]]> 0.7
[0033] Weigh the above-mentioned amounts of silicon dioxide, lithium carbonate, aluminum oxide, rubidium carbonate, diammonium hydrogen phosphate, lanthanum oxide, cerium oxide and zirconium oxide raw materials, transfer them to an agate mortar and grind them to mix the raw materials thoroughly and evenly, transfer the evenly mixed raw materials to a corundum crucible, and keep them warm at 1500° C. in a muffle furnace for 60 min. After the insulation time, the glass liquid is quenched with water, and the glass blocks obtained by water quenching are dried in an oven at 80° C. for 30 min, and then ground evenly in an agate mortar to obtain glass powder.
[0034] Example 2
[0035] Table 2
[0036] raw material Weight(g) KBr 0.011 Cb 0.076 <![CDATA[PbBr 2 ]]> 0.164 Lithium disilicate glass powder 0.5
[0037] The K 0.2 Cs 0.8 PbB 3 The quantum dot glass ceramic material comprises the following steps:
[0038] The above amounts of potassium bromide, cesium bromide and lead bromide raw materials were mixed evenly in an agate mortar, and then 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 600° C. for 3 h to obtain K 0.2 Cs 0.8 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 50% of the mass of the lithium disilicate glass.
[0039] The green emission peak of the sample of Example 2 is narrow, with a peak value at 518 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting green light of a certain intensity, which can still maintain a certain intensity in polar solvents.
[0040] Example 3
[0041] Table 3
[0042] raw material Weight(g) KBr 0.013 Cb 0.072 <![CDATA[PbBr 2 ]]> 0.165 Lithium disilicate glass powder 0.5
[0043] The K 0.25 Cs 0.75 PbB 3 The quantum dot glass ceramic material comprises the following steps:
[0044] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 600°C for 3 h to obtain K 0.25 Cs 0.75 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 50% of the mass of the lithium disilicate glass.
[0045] The green emission peak of the sample of Example 3 is narrow, with a peak value at 517 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting relatively bright green light, and can still maintain a certain intensity in polar solvents.
[0046] Example 4
[0047] Table 4
[0048]
[0049]
[0050] The K 0.3 Cs 0.7 PbB 3The quantum dot glass ceramic material comprises the following steps:
[0051] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 600°C for 3 h to obtain K 0.3 Cs 0.7 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 50% of the mass of the lithium disilicate glass.
[0052] The green emission peak of the sample of Example 4 is narrow, with a peak value at 518 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting extremely bright green light, which can still maintain a certain intensity in polar solvents.
[0053] Example 5
[0054] Table 5
[0055] raw material Weight(g) KBr 0.022 Cb 0.059 <![CDATA[PbBr 2 ]]> 0.169 Lithium disilicate glass powder 0.5
[0056] The K 0.4 Cs 0.6 PbB 3 The quantum dot glass ceramic material comprises the following steps:
[0057] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 600°C for 3 h to obtain K 0.4 Cs 0.6 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 50% of the mass of the lithium disilicate glass.
[0058] The green emission peak of the sample of Example 5 is narrow, with a peak value at 518 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting extremely bright green light, which can still maintain a certain intensity in polar solvents.
[0059] Example 6
[0060] Table 6
[0061] raw material Weight(g) KBr 0.013 Cb 0.072 <![CDATA[PbBr 2 ]]> 0.165 Lithium disilicate glass powder 0.5
[0062] The K 0.25 Cs 0.75 PbB 3The quantum dot glass ceramic material comprises the following steps:
[0063] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 500° C. for 3 h to obtain K 0.25 Cs 0.75 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 50% of the mass of the lithium disilicate glass.
[0064] The green emission peak of the sample of Example 6 is narrow, with a peak value at 511 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting green light of a certain intensity, which can still maintain a certain intensity in polar solvents.
[0065] Example 7
[0066] Table 7
[0067] raw material Weight(g) KBr 0.013 Cb 0.072 <![CDATA[PbBr 2 ]]> 0.165 Lithium disilicate glass powder 0.5
[0068] The high temperature solid phase method was used to prepare K 0.25 Cs 0.75 PbB 3 The quantum dot glass ceramic material comprises the following steps:
[0069] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 700°C for 3 h to obtain K 0.25 Cs 0.75 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 50% of the mass of the lithium disilicate glass.
[0070] The green emission peak of the sample of Example 7 is narrow, with a peak value at 519 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting green light of a certain intensity, which can still maintain a certain intensity in polar solvents.
[0071] Example 8
[0072] Table 8
[0073] raw material Weight(g) KBr 0.013 Cb 0.072 <![CDATA[PbBr 2 ]]> 0.165 Lithium disilicate glass powder 0.5
[0074] The high temperature solid phase method was used to prepare K 0.25 Cs 0.75 PbB 3The quantum dot glass ceramic material comprises the following steps:
[0075] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 600°C for 2 h to obtain K 0.25 Cs 0.75 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 50% of the mass of the lithium disilicate glass.
[0076] The green emission peak of the sample of Example 8 is narrow, with a peak value at 515 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting green light of a certain intensity, which can still maintain a certain intensity in polar solvents.
[0077] Example 9
[0078] Table 9
[0079]
[0080]
[0081] The K 0.25 Cs 0.75 PbB 3 The quantum dot glass ceramic material comprises the following steps:
[0082] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of the lithium disilicate glass powder obtained in Example 1 was added, and the mixture was transferred to a glass slide after being ground evenly, and then placed in a muffle furnace and sintered at 600° C. for 4 h to obtain K 0.25 Cs 0.75 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 50% of the mass of the lithium disilicate glass.
[0083] The green emission peak of the sample of Example 9 is narrow, with a peak value at 519 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting relatively low-intensity green light, which can still maintain a certain intensity in polar solvents.
[0084] Example 10
[0085] Table 10
[0086] raw material Weight(g) KBr 0.003 Cb 0.014 <![CDATA[PbBr 2 ]]> 0.033 Lithium disilicate glass powder 0.5
[0087] The K0.25 Cs 0.75 PbB 3 The quantum dot glass ceramic material comprises the following steps:
[0088] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 600°C for 3 h to obtain K 0.25 Cs 0.75 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 10% of the mass of the lithium disilicate glass.
[0089] The green emission peak of the sample of Example 10 is narrow, with a peak value at 519 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting relatively low-intensity green light, which can still maintain a certain intensity in polar solvents.
[0090] Embodiment 11
[0091] Table 11
[0092] raw material Weight(g) KBr 0.008 Cb 0.043 <![CDATA[PbBr 2 ]]> 0.099 Lithium disilicate glass powder 0.5
[0093] The high temperature solid phase method was used to prepare K 0.25 Cs 0.75 PbB 3 The quantum dot glass ceramic material comprises the following steps:
[0094] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 600°C for 3 h to obtain K 0.25 Cs 0.75 PbB 3 A quantum dot glass composite luminescent material, wherein the mass of the perovskite quantum dots is 30% of the mass of the lithium disilicate glass.
[0095] The green emission peak of the sample of Example 11 is narrow, with a peak value at 518 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting relatively low-intensity green light, which can still maintain a certain intensity in polar solvents.
[0096] Example 12
[0097] Table 12
[0098] raw material Weight(g) KBr 0.019 Cb 0.100 <![CDATA[PbBr 2 ]]> 0.231 Lithium disilicate glass powder 0.5
[0099] The K 0.25 Cs 0.75 PbB 3 The quantum dot glass ceramic material comprises the following steps:
[0100] The above amounts of potassium bromide, cesium bromide and lead bromide were mixed evenly in an agate mortar, and 0.5 g of lithium disilicate glass powder obtained in Example 1 was added, and after being ground evenly, it was transferred to a glass slide and placed in a muffle furnace for sintering at 600°C for 3 h to obtain K 0.25 Cs 0.75 PbB 3 Quantum dot glass composite luminescent material, wherein the mass of perovskite quantum dots is 70% of the mass of lithium disilicate glass.
[0101] The green emission peak of the sample of Example 12 is narrow, with a peak value at 519 nm and a half-peak width of only 20 to 50 nm; the excitation peak covers the 275 to 450 nm region, emitting relatively low-intensity green light, which can still maintain a certain intensity in polar solvents.
[0102] Figure 1 The HRTEM image and particle size statistics of the sample obtained in Example 3 are as follows: Figure 1 It can be seen that the glass matrix has a good coating effect, and the spherical quantum dots are clearly visible in the glass matrix.
[0103] Figure 2 The excitation spectra of the samples prepared in Example 3, Example 6 and Example 7 under 517 nm wavelength monitoring and the emission spectra under 365 nm wavelength excitation are as follows: Figure 3 It can be seen that the peak of the samples of perovskite quantum dots at different temperatures under the excitation of 365nm near-ultraviolet light wavelength is located at around 517nm, and its half-peak width is 20 to 50nm.
[0104] Figure 3 The bright green light generated when Example 3 of the present invention is mixed with UV-curable organic silica gel and packaged in a 365nm UV chip and then excited.
[0105] Figure 4 The green light emitted by Example 3 of the present invention after being mixed with deionized water under irradiation with a 365nm ultraviolet lamp.
[0106] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A perovskite quantum dot glass composite luminescent material, characterized in that: The luminescent material comprises perovskite quantum dots and lithium disilicate glass ceramics, wherein the chemical formula of the perovskite quantum dots is K x Cs 1-x PbBr3, 0.2≤x≤0.4, the mass of the perovskite quantum dots is 10-70% of the mass of the lithium disilicate glass ceramic.
2. The composite luminescent material according to claim 1, characterized in that: The average particle size of the perovskite quantum dots is 2 to 7 nm.
3. A method for preparing the composite luminescent material according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: (1) Grinding Li2CO3, Rb2CO3, NH4H2PO4, Al2O3, SiO2, La2O3, CeO2, and ZrO2, and mixing them uniformly to obtain a glass ceramic raw material; (2) melting the glass ceramic raw material obtained in step (1) in a muffle furnace to obtain molten glass, then quenching the molten glass with water to obtain a glass block, drying the glass block, and grinding it to obtain glass powder; (3) The glass powder obtained in step (2) is mixed with KBr, CsBr and PbBr2 and ground evenly, and heat-treated in a muffle furnace to obtain a perovskite quantum dot glass composite luminescent material.
4. The preparation method according to claim 3, characterized in that: In step (2), the melting temperature is 1200-1800° C., and the insulation time is 30-80 min.
5. The preparation method according to claim 3, characterized in that: In step (3), the heat treatment temperature is 500-700° C., and the heat treatment time is 180-300 min.
6. The preparation method according to claim 3, characterized in that: The mass ratio of Li2CO3, Rb2CO3, NH4H2PO4, Al2O3, SiO2, La2O3, CeO2 and ZrO2 is 10-15:10-15:5-10:1-5:45-60:5-15:1-5:1-5; The mass ratio of the glass powder, KBr, CsBr and PbBr2 is 58.8-91:0.5-2.2:2.5-11.8:6-27.
2.
7. Use of the composite luminescent material according to any one of claims 1 to 2 or the composite luminescent material prepared by the preparation method according to any one of claims 3 to 6 in lighting devices and display devices.
Citation Information
Patent Citations
K<x>Cs<1-x>PbBr3 glass-ceramic and preparation method thereof
CN109761498A
Fluorescent lithium silicate glass material and preparation method and applications thereof
CN110981204A
Starting glass, lithium silicate glass with core and preparation method and application of lithium silicate glass
CN112551894A
CsPbBr3 / Cs4PbBr6 quantum dot glass ceramic composite luminescent material as well as preparation method and application thereof
CN117164240A
Method for regulating and controlling photocatalytic performance of metal halide perovskite through alkali metal A-site doping
CN117443416A